Food Contaminant Components: Source, Detection, Toxicity and Removal - Peng, Dapeng; Qian, Yongzhong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The contaminants in food (e.g., heavy metals, foodborne pathogenic microorganisms, pesticides, veterinary drugs/antibiotics, toxins, prohibited additives, and allergens) can seriously threaten the 'health of human beings. In recent years, research on the source, detection, toxicity, and removal of food contaminant components has undergone rapid development and achieved tremendous progress through the painstaking efforts of researchers. Therefore, the aim of this Special Issue is to provide a broader perspective of the latest advances in the source, detection, toxicity, and removal of food contaminant components. In this Special Issue, we aim to address: 1) Where do these contaminant components come from? How can we detect these contaminant components? How toxic are these contaminant components? How can we remove these contaminant components? Methodological advances in all areas of food contaminant components, from fundamental research to applied research, can be covered. We welcomed both original research and review articles on topics including, but not limited to: food contaminants; sources; metabolism; biotransformation; toxicity; elimination; excretion; detection